Educational training program to increase the moderate to vigorous physical activity index in physical education teachers - Javier Arturo Hall-López (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Objective: To design and evaluate a training program to increase the moderate to vigorous physical activity index in physical education teachers. Method: the volunteer subjects participated in the educational training program whose goal was to obtain competences on how to create a pedagogical climate in physical education class oriented to the participation of students in moderate to vigorous physical activity at least 50% of the class evaluated quantitatively using the system for observing fitness instruction time (SOFIT), during their university studies and when they have graduated as physical education teachers. Results: The physical activity index increased from 36.6% to 61.2%. Conclusions: The application of the program showed effectiveness with didactic strategies to involve the student in moderate to vigorous physical activity as established by the World Health Organization.